2017
DOI: 10.17352/2455-5460.000019
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between maladaptive cognitive emotion regulation strategies and psychopathology in adolescents from Bangladesh

Abstract: Introduction: Psychopathology of adolescents in developing countries such as Bangladesh is a neglected problem, which should get more attention, especially with a focus on Þ nding targets for prevention and intervention. Aim of the study was to study relationships between cognitive emotion regulation strategies and psychopathology in Bengali adolescents. Methods:The sample consisted of 340 12-to-18-year old adolescents from Bangladesh. The Cognitive Emotion Regulation Questionnaire (CERQ) was used to measure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
12
0
4
Order By: Relevance
“…The present study also revealed that MBCT increases the use of cognitive regulation strategies and reduces the use of negative emotional regulation strategies in people undergoing MMT. These results are in line with those of Schmidt et al, (2018), Garnefski, Hossain, & Kraaij, (2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also revealed that MBCT increases the use of cognitive regulation strategies and reduces the use of negative emotional regulation strategies in people undergoing MMT. These results are in line with those of Schmidt et al, (2018), Garnefski, Hossain, & Kraaij, (2017).…”
Section: Discussionsupporting
confidence: 92%
“…They believe that the mindfulness involves a variety of psychological mechanisms which reduce distress. These mechanisms are rethinking or reformatting experiences from a better metacognitive perspective, improving emotions, selfregulation, increasing mental flexibility, and desensitizing empathic experiences through the perceived lack of threat (Garnefski et al, 2017). It is likely that these new emotional and cognitive aspects be a neuroscience framework, through which the mindfulness is related to substance abuse (Garnefski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rezultati o zastupljenosti strategija kognitivne emocionalne regulacije su pokazali da su kod adolescenata najzastupljenije strategije planiranje i pozitivna preformulacija; slede ih ruminacija, prihvatanje, stavljanje u perspektivu i pozitivno refokusiranje; dok su samo-okrivljavanje, katastrofiziranje i okrivljavanje drugih strategije koje adolescenti najređe koriste. Ovi nalazi su u skladu sa rezultatima većeg drugih studija na uzorcima adolescenata (Garnefski et al, 2017). Naime, ispitanici iz ovog uzorka nalaze se u periodu ulaska u srednju adolescenciju, kada opada zavisnost od neposredne emocionalne podrške roditelja, a jačaju sopstvene strategije emocionalne regulacije.…”
Section: Diskusijaunclassified
“…Several studies have demonstrated an association between cognitive emotional regulation strategies and depressive symptomatology in adolescence, with positive relationships with strategies like rumination, catastrophizing and self-blame, and negative relationships with more adaptive strategies, like positive reappraisal (d 'Acremont & Van der Linden, 2007;Garnefski, Boon, & Kraaij, 2003;Garnefski, Hossain, & Kraaij, 2017;Garnefski & Kraaij, 2006;Garnefski & Kraaij, 2014;Garnefski & Kraaij, 2016;Garnefski, Kraaij, & van Etten, 2005;Garnefski, Legerstee, Kraaij, Van den Kommer, & Teerds, 2002;Kraaij & Garnefski, 2012;Kraaij et al, 2003;Öngen, 2010). Indeed, studies that analysed the factorial https: //dx.doi.org/10.15405/epsbs.2019.02.02.42 Corresponding Author: Ana Paula Matos Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 382 structure of CERQ verified a division between theoretically more adaptive strategies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…putting into perspective, positive refocusing, positive reappraisal and refocus on planning) and less adaptive strategies (e.g. self-blame, blaming others, rumination and catastrophizing) (d 'Acremont & Van der Linden, 2007;Garnefski et al, 2017;Garnefski, Kraaij, & Spinhoven, 2001;Öngen, 2010). In respect to the acceptance strategy, while some studies consider it as a more adaptive strategy (d 'Acremont & Van der Linden, 2007;Garnefski et al, 2001), other studies verified that this strategy was positively associated with depressive symptomatology (Garnefski & Kraaij, 2006;Garnefski & Kraaij, 2016).…”
Section: Introductionmentioning
confidence: 99%